Value of Ultrasonography on Diagnosis and Assessment of Pain and Grip Strength in Patients with Lateral Epicondylitis - Serdar Tarhan; Zeliha Ünlü; Gülgün Yılmaz Ovalı; Yüksel Pabuşçu (Archives of Rheumatology, 2009)
Objective: Lateral epicondylitis (LE) is generally diagnosed clinically. Ultrasonography (US) can provide useful information about the location, extent, and severity of LE. Our objective was to use US to confirm LE and to investigate the relationships between pain, grip strength, physical examination, and disability in these patients. Material and Methods: Fifty-two patients with unilateral LE were examined by US. Pain and functional status were assessed using a visual analog scale (VAS), physical functioning and bodily pain scales of the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36), and a patient-rated forearm evaluation questionnaire (PRFEQ). Grip strength and manual tests for LE were evaluated. Results: Clinical diagnosis of LE was confirmed by US in 28 (53.8%) patients. Our results showed close associations between clinical examination findings and SF-36 and PRFEQ assessments with pain in patients who had sonographic abnormalities. Grip strength was also correlated with clinical and functional evaluations in these cases. Conclusion: We concluded that evaluation of disability in LE requires methods different from those included in the traditional clinical examination. Pain and grip strength measurements provide numerical and quantitative data for evaluation of severity and disability in patients with sonographic findings of LE. (Turk J Rheumatol 2009; 24: 123-30)